2023
DOI: 10.3390/biom13071028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Peptides with Dual Properties for Treating Pseudomonas aeruginosa Keratitis: Antibacterial and Corneal Wound Healing

Abstract: The corneal epithelium is a layer in the anterior part of eye that contributes to light refraction onto the retina and to the ocular immune defense. Although an intact corneal epithelium is an excellent barrier against microbial pathogens and injuries, corneal abrasions can lead to devastating eye infections. Among them, Pseudomonas aeruginosa-associated keratitis often results in severe deterioration of the corneal tissue and even blindness. Hence, the discovery of new drugs able not only to eradicate ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…The synthetic AMP Esc(1-21) has 21 residues and is generated from Esculentin-1A, the parent AMP. Its diastereomer is Esc(1-21)-1c [ 60 ]. A unique synthetic AMP called HX-12C was created to hasten the healing of wounds [ 61 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthetic AMP Esc(1-21) has 21 residues and is generated from Esculentin-1A, the parent AMP. Its diastereomer is Esc(1-21)-1c [ 60 ]. A unique synthetic AMP called HX-12C was created to hasten the healing of wounds [ 61 ].…”
Section: Reviewmentioning
confidence: 99%
“…Esc(1-21) and Esc(1-21)-1c were tested for their ability to promote wound healing using human corneal epithelial cells (HCECs) in an in vitro scratch assay [ 60 ]. The data revealed that both peptides helped close the gap area in a way that was dependent on time and dose.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations